Testing phenol formaldehyde composite insulation material for conservation purposes - Tabea Rude (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This investigation related to the degradation of phenol formaldehyde based electrical insulation materials in close mechanical contact with CZ108 brass in a Post Office Type 36 time transmitter, an electromechanical clock. Through testing of the two material types, the project exposed differences in degradation properties due to different manufacturing methods of the plastic component. Preventive conservation advice was then synthesised from the outcome.